Transcriptome Analysis of mRNAs and Long Non-Coding RNAs During Subsequent Embryo Development of Porcine Cloned Zygotes After Vitrification - Xiang, Decai; Jia, Baoyu; Guo, Jianxiong; Shao, Qingyong; Hong, Qionghua; Wei, Hongjiang; Quan, Guobo; Wu, Guoquan (Frontiers in Genetics, 2021)
Cryopreservation of porcine cloned zygotes has important implications for biotechnology and biomedicine research; however, lower embryo developmental potential remains an urgent problem to be resolved. For exploring the sublethal cryodamages during embryo development, this study was designed to acquire the mRNA and long non-coding RNA (lncRNA) profiles of 2-cells, 4-cells and blastocysts derived from vitrified porcine cloned zygotes using transcriptome sequencing. We identified 167 differentially expressed (DE) mRNAs and 516 DE lncRNAs in 2-cell stage, 469 DE mRNAs and 565 lncRNAs in 4-cell stage, and 389 DE mRNAs and 816 DE lncRNAs in blastocyst stage. Functional enrichment analysis revealed that the DE mRNAs during embryo development were involved in many regulatory mechanisms related to cell cycle, cell proliferation, apoptosis, metabolism and others. Moreover, the target genes of DE lncRNAs in the three embryonic stages were also enriched in many key GO terms or pathways such as ‘defense response’, ‘linoleic acid metabolic process’, ‘embryonic axis specification’, ‘negative regulation of protein neddylation’, etc. In conclusion, the present study provided comprehensive transcriptomic data about mRNAs and lncRNAs for the vitrified porcine cloned zygotes during different developmental stages, which contributed to further understand the potential cryodamage mechanisms responsible for impaired embryo development.